The Formation of the Chemical Composition of Karymsky R. Water As Affected by Hydrothermal and Volcanic Activity in Kamchatka - Kalacheva E.G.; Melnikov D.V.; Dolgaya A.A.; Voloshina E.V. (My University, 2024)
This paper examines the Karymsky Volcanic Center to estimate how much volcanic and hydrothermal activity affects the chemical composition of river water. We evaluate the volumes of major and trace elements coming to the Pacific Ocean via the Karymsky River. We assess the quality of river water in compliance with the regulations for potable water, water used for household work, and in fisheries. It is shown that the formation of ion load of the river water mostly occurs by inflow of thermal waters, as well as due to water-soluble complexes of ashes discharged by Karymsky Volcano and coming to the catchment area of the river. The annual volume of dissolved material transported by the river to the Kronotsky Bay of the Pacific Ocean amounts to more than 90 kilotons.
Keywords: 38.33.19 Геохимия природных вод и рассолов; 38.37.25 Вулканология; Карымский